Positioning Climate Therapy Stays as a Health Tourism Product: An Evidence-Based Approach - Maurizio Droli; Lorena Bašan; Fabio Giuseppe Vassallo (Ital Publication, 2022)
Background: The relationship between Length Of Stay (LOS) and Metres Above Sea Level (MASL) of Climate Therapy Stays (CTSs) and their therapeutic effectiveness and efficiency has been under-researched in the last four decades. As a consequence, the potentials of short-term and low-altitude CTSs remain unknown. Objectives: The purpose of this study is twofold. Firstly, it aims to ascertain whether LOS and MASL are related to the percentage change of Forced Expiratory Volume in 1 second (FEV1) and the percentage change of FEV1 Compound Daily Improvement Rate (FEV1 CDIR % Change). Secondly, it aims to provide an evidence-based positioning of CTSs by considering the same specific variables. Methods/Analysis: The study focuses on young people (age ˂18) who have asthma problems. The Resource-Based Theory, postulating the valuability of natural resources generating above-average benefits, has been adopted as a conceptual lens. Primary studies carried out in eastern and western European countries and separately reviewed have been considered jointly. Spearman’s rank correlation coefficient was used to determine the relationship between LOS and MASL of CTSs with FEV1Change (%) and FEV1Change CDIR (%) as indicators of health improvements. The descriptive statistics were implemented in calculating standardized and aggregated values. Findings: Negative and significant relationships have been highlighted between FEV1 Change (%) and MASL and between FEV1 Change CDIR % and LOS. In other words, subjects can achieve significant health improvements even by experiencing very short climate therapy stays at very low altitude mountain centres. Considering the FEV1Change (%) and the FEV1 Change CDIR (%) of climate stays by duration and elevation, the evidence-based knowledge platform has been established as a possible framework for developing an evidence-based marketing strategy for new health tourism products. Novelty/Improvement:Notwithstanding the need for further research, the metrics facilitating interdisciplinary, human health and economic studies have been devised. Further research on the effects of low altitude climate therapy stays could help define the healing potentials of macro and microclimatic conditions as potentially valuable ‘health devices’ for those suffering from respiratory diseases living in the COVID-19 era. Quantifying these effects through further studies, an evidence-based approach to formulating marketing strategies may be devised, useful both for supporting public health provision and policies, and for facilitating practitioners in health tourism interested in offering nature-based activities for their clients. Doi: 10.28991/ESJ-2022-06-02-04 Full Text: PDF